1986
DOI: 10.1111/j.1574-6968.1986.tb01708.x
|View full text |Cite
|
Sign up to set email alerts
|

Proline reduction byClostridium sporogenesis coupled to vectorial proton ejection

Abstract: The reduction of proline by Clostridium sporogenes NCIB8053 is coupled to transmembrane proton translocation in an uncoupler‐sensitive fashion (and might therefore conserve free energy). This finding serves to explain the increase in the growth yield of this organism when proline is added to a defined growth medium containing glucose as the catabolic substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…First proline racemase (PrdF) converts L -proline into D -proline (Wu and Hurdle, 2014). Already in the eighties it was shown that proline reduction is coupled to proton motive force generation (Lovitt et al, 1986). However, the enzyme complex does not reduce ferredoxin and was proposed to directly interact with the membrane-localized, proton/sodium pumping Rnf complex (Jackson et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…First proline racemase (PrdF) converts L -proline into D -proline (Wu and Hurdle, 2014). Already in the eighties it was shown that proline reduction is coupled to proton motive force generation (Lovitt et al, 1986). However, the enzyme complex does not reduce ferredoxin and was proposed to directly interact with the membrane-localized, proton/sodium pumping Rnf complex (Jackson et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…In C. sporogenes , the reduction of D-proline was described to be coupled to transmembrane proton ejection. However, it has not been demonstrated whether this proton gradient is coupled to ATP synthesis [50]. This is possibly due to a very low proton ejection.…”
Section: Resultsmentioning
confidence: 99%
“…Glycine reduction results in production of acetyl phosphate, and thus ATP synthesis via substrate-level phosphorylation [40, 41]. Reduction of proline has been tied to membrane gradients [42]. The enzymes that catalyze these reactions in C. difficile are glycine reductase and D-proline reductase respectively.…”
Section: Resultsmentioning
confidence: 99%